PERMOHONAN EKSEKUSI NAFKAH ISTRI PASCA PERCERAIAN - Rachmat Taibu; Mastina (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2026)
The purpose of this study is to determine the application for the execution of wife's maintenance after divorce. To determine the inhibiting factors in the execution of wife's maintenance after divorce. This study adopts normative law research using normative case studies in the form of legal products, for example studying the Law. The main subject of the study is the law that is conceptualized as a norm or rule that applies in society and becomes a reference for everyone's behavior. So that normative legal research focuses on the inventory of positive law. The method of collecting legal materials that will be used in this study is through library research. The data analysis used in this study is qualitative descriptive data analysis, namely data obtained after being systematically compiled, to then be analyzed qualitatively descriptively in the form of descriptions. The results of the study show that based on the implementation of the divorce decision, regarding the wife's maintenance after the divorce takes precedence over the pronouncement of the divorce vow, it is based on SEMA no. 1 of 2017.regarding the Implementation of the Formulation of the Results of the Plenary Meeting of the Supreme Court Chamber in 2017 as a Guideline for the Implementation of Duties for the Court which states that the payment of wife's maintenance after divorce is paid before the declaration of divorce. This is done to protect the rights of women who are divorced by their husbands and also to fill the legal vacuum in Indonesia. If within a period of 6 (six) months from the date of the determination of the declaration of divorce, the husband or his attorney does not carry out the declaration of divorce in front of the court, then the legal force of the determination is void, and divorce cannot be submitted again based on the same legal reasons (Article 70 paragraph (6) of Law No. 7 of 1989 which has been amended by Law No. 3 of 2006). After the divorce vow is pronounced, the clerk is obliged to provide a Divorce Certificate as proof to both parties, no later than 7 (seven) days after the determination of the divorce vow (Article 84 paragraph (4) of Law No. 7 of 1989 which has been amended by Law No. 3 of 2006). Inhibiting factors in the execution of the wife's nasfakah after divorce The absence of firm and clear rules for husbands who do not carry out the divorce vow, decisions that cannot be executed and the low level of legal awareness and legal knowledge in society.